Comparative analysis for quantification of Citrus Variegated Chlorosis in the field (Scientia Agricola, 2011)
Citrus Variegated Chlorosis (CVC) caused by Xylella fastidiosa is one of the most important diseases for Brazilian citriculture. The CVC is a vascular disease with a long incubation period and symptoms similar to other disorders, and this factors difficult the CVC quantification in the field. Two methods of CVC assessment were compared in this study. The first method was based on a descriptive rating scale with four ratings, commonly used for the disease quantification. The second one was based on the incidence of symptomatic branches. The quantification of CVC through these two methods was carried out in a 10-year-old 'Natal' sweet orange orchard. The descriptive scale considered the symptoms of the entire plant. The disease incidence was evaluated in 36 branches in each plant. The assessments were conducted by three raters in 144 plants in July 2006 and July 2007 as well as in March and November 2008. The descriptive scale did not allow an accurate assessment and resulted in a moderate strength of agreement among the raters. On the other hand, the incidence quantification of CVC through the symptomatic branches showed high repeatability among the raters. We suggest the use of incidence of symptomatic branches as variable for CVC quantification.